Application Of Infra Fiber In Making Nets And Its Efficiency As An Erosion Preventative On Mountain Slope - Arpan Hala (BULETIN FISIKA, 2026)
This study aims to analyze the application of palm fiber (Arenga pinnata) in the production of fiber nets and to evaluate their efficiency as an erosion control method on mountainous slopes with a 40° inclination. The palm fiber net was manufactured from natural palm fibers woven into a mesh size of 5 cm × 5 cm and applied as a surface cover on sloping land. The research was conducted in Binajaya Village, Tolangohula District, Gorontalo Regency, from October to December 2024. The research methodology included the fabrication and vertical installation of palm fiber nets following the slope direction, the establishment of experimental plots, and the measurement of soil loss caused by surface runoff. Plots equipped with palm fiber nets were compared with untreated plots as control samples. Rainfall data were obtained from NASA POWER and analyzed together with soil erosion data collected from five rainfall events. The results obtained in this study were, in plot 1 using the net obtained the highest eroded mass of 8.2 kg and the lowest eroded mass of 1.7 kg, and plot 2 without using the net with the highest eroded mass of 23.8 kg and the lowest eroded mass of 5.6 kg. The efficiency of the palm fiber net was 72.1%. These findings demonstrate palm fiber nets effectively reduce soil erosion by decreasing rainfall impact energy, slowing surface runoff, and retaining soil particles. Therefore, palm fiber nets have strong potential as an environmentally friendly, natural-based soil conservation method for erosion control on steep slopes.